ANALISIS BEBAN KERJA PEGAWAI BAGIAN SEKRETARIAT DINAS KESEHATAN KABUPATEN BENGKALIS TAHUN 2013 - Akhmad Mukhlis; Nazrantika Sunarto (Inovbiz: Jurnal Inovasi Bisnis, 2015)
Abstract :The purposes of this research are to analyze the work load of employees at Secretariat Division of Health Department of Bengkalis Regency and also to counts the need of employees accordance with recent work load. This type of research is a descriptive research. The   result of this research discusses about work load happen at The Secretariat Division of Health Department of Bengkalis Regency  that  consisting  of  General  Administration  of  Sub.  Administration Division, Sub. Planning And Programing Division, And Sub. Accounting and Equipment Division. With conclusion that was become work load that significan on sectioned secretariat which is General Administration of Sub. Administration Division needs 10 employees, Sub. Planning and Programing needs 8 employees. But, on Sub. Accounting and Equipment exceeds requirement for from amount 14 current employees just be needed 13 employees. Key Words: Job Describtions, Work Load